Genetic polymorphisms of patients on stable warfarin maintenance therapy in a Ghanaian population. (December 2016) - Kudzi, William; Ahorhorlu, Samuel; Dzudzor, Bartholomew; Olayemi, Edeghonghon; Nartey, Edmund; Asmah, Richard
Abstract Background Warfarin is a widely prescribed anticoagulant with narrow therapeutic window for thromboembolic events. Warfarin displays large individual variability in dose requirements. The purpose of this study is to assess the contribution of patient-specific and genetic risk factors to dose requirements of patients on either high or low warfarin maintenance dose in Ghana. Blood samples were collected from 141 (62 males, 79 females) Ghanaian patients on stable warfarin dose to determine their INR. Influence of patient specific factors and gene variations withinVKORC1, CYP2C9 andCYP4F2 were determined in patients on either high or low warfarin maintenance dose. Results One hundred and forty-one patients took part in the study with 79 (56%) participants being Female. The median age of the study participants was 48 years [IQR: 34–58]. The median duration for patients to be on warfarin therapy was 24 months [IQR: 10–72]. Majority of the study participants (80.9%, n = 114) did not have any side effects to warfarin.CYP2C9* 2 andCYP2C9* 3 variant alleles were not detected.VKORC1 variant allele was observed at 6% andCYP4F2 variant allele was observed at 41%. Duration of patients on warfarin therapy was marginally associated with high warfarin dose (adjusted OR = 1.01 [95% CI 1.00–1.02], p = 0.033) while the odds of heterozygous individuals (G/A) for VKORC1 gene to have high warfarin dose compared to persons with homozygous (G/G) (adjusted OR = 0.06 [95% CI 0.01–0.63], p = 0.019). Age, gender, diagnosis, presence of side effects and other medications were not associated with warfarin dose (p = 0.05). Conclusion This study provides data onVKORC1 andCYP4F2 variants among an indigenous African population. Duration of patients on warfarin therapy was marginally associated with high warfarin dose.CYP2C9 *2 and *3 variants were not detected and may not be the most important genetic factor for warfarin maintenance dose among Ghanaians.